Avaliação do desempenho de sistema de transportes público utilizando indicadores de mobilidade urbana sustentável - Costa, Priscila Bahia (2016)
The greatest challenge in Brazilian cities today has been to face long traffic jams, since most people stop using collective transportation to prioritize the practicality of individual motorized transportation. Encouraging the improvement of public transport is therefore essential to minimize the problem. Considering this scenario, this research aims to evaluate the performance of the Public Transport System by Bus of the Metropolitan Region of Greater Vitoria region using indicators of sustainable urban mobility and also to make a comparative analysis with transportation systems from other regions of the Country. The IMUS (Urban Sustainable Mobility Index), developed by Costa (2008), a tool to support public policies, which helps in directing actions and, mainly, in the identification of areas that require Investments. The index consists of 87 indicators, but since the focus of this research is public transport, only 22 were directly linked to the theme. In the search for the regions to be analyzed comparatively with the Metropolitan Region of Greater Vitoria, some criteria were considered, such as the use of sustainable urban mobility index, availability of data, similarity with transport used in the RMGV and the existing population in the Region to be chosen. The results show that the RMGV performed poorly in some indicators when compared to the other regions chosen for comparison. It is possible to analyze the positive and negative points of the indicators, allowing the managers to elaborate measures and actions to solve the deficit points and the improvement of the indicators that presented good performance. It is suggested that there may be greater investments in the Origin-Destination research, since it is important to present instruments that allow transportation planning.